Bracia polscy a Oświecenie - Sztajer, Sławomir (Humaniora. Czasopismo Internetowe, 2023)
The paper discusses the philosophical and theological ideas of the Polish Brethren, a nontrinitarian reformed church in 16th Century Poland. Due to religious persecution, the Polish Brethren, also known as Socinians or Polish Arians, were forced to leave the Polish-Lithuanian Commonwealth and seek refuge in other European countries. Their legacy had a significant impact on the development of Enlightenment thought in Europe and inspired legislators both in Europe and America. The ideas developed by the Polish Brethren had a significant impact on the formation of Enlightenment ideas and thought trends, such as rationalism and deism referring to rationalism, as well as tolerance, particularly religious tolerance, and secularism manifesting in the separation of religious and secular institutions. Moreover, the ideas of Polish Arianism, which fascinated Enlightenment thinkers, became part of the cultural mainstream and were reflected in modern Western state institutions.